The Effect of Website-Based Puzzle Media on the Science and Social Studies (IPAS) Learning Outcomes of Fifth-Grade Students at SD Negeri 109 Cappagalung, South Sinjai District, Sinjai Regency - Rosmalah, Rosmalah; Jauhar, Sitti; Wiranti, Nova Resti (International Journal of Elementary School Teacher, 2025)
This study is a quantitative pre-experimental study that aims to analyze the effect of using website-based puzzle media on the learning outcomes of Fifth Grade Students of Elementary School 109 Cappagalung, South Sinjai District, Sinjai Regency. This study uses a One Group Pre-test-Post-test design. The population in this study were 17 fifth grade students of Elementary School 109 Cappagalung, with a sampling technique using a saturated sampling technique. Data collection techniques were carried out through learning outcome tests before and after using website-based puzzle media. Hypothesis testing using Paired Sample t-Test with the help of IBM SPSS Statistic Version 26 program. The data analysis techniques used are descriptive statistical analysis techniques and inferential statistical analysis techniques. Based on the descriptive statistical analysis, the average pretest value of 43.92 is in the less category while the average posttest of 76.46 is in the good category. The data obtained were then analyzed using the Paired Sample t-Test with a significance level of 5%. From the data results obtained tcount (10.985) (>) ttable (2.11991). Thus, H₀ is rejected and H₁ is accepted, it can be concluded that website-based puzzle media has a significant effect on the learning outcomes of science at SD Negeri 109 Cappagalung, South Sinjai District, Sinjai Regency.